2003
DOI: 10.1080/00365520310004515
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Duodenal Adenoma in Celiac Disease

Abstract: We did not find a significantly increased risk of duodenal adenoma in celiac patients compared to a non-celiac endoscoped population. Thus, despite the previously described elevated risk of small-bowel adenocarcinoma in these patients, routine endoscopic examination of the duodenum may not be adequate for screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In a series of 94 cases of small bowel adenocarcinoma from the Mayo Clinic, evidence of flat dysplasia at the tumor margin was noted in 50% of cases associated with celiac disease [ 18 ]. Although some authors suggested that carcinomas in celiac disease may arise from adenomatous polyp [ 19 ], others found no increased incidence of duodenal adenomas in celiac disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 94 cases of small bowel adenocarcinoma from the Mayo Clinic, evidence of flat dysplasia at the tumor margin was noted in 50% of cases associated with celiac disease [ 18 ]. Although some authors suggested that carcinomas in celiac disease may arise from adenomatous polyp [ 19 ], others found no increased incidence of duodenal adenomas in celiac disease [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another hypothesis which has been postulated is that small bowel adenocarcinoma in CD arises through an adenoma-carcinoma sequence [13]. However, currently there are conflicting results regarding this hypothesis [14,15,16,17]. …”
Section: Discussionmentioning
confidence: 99%
“…Small bowel adenocarcinoma is normally rare, but may be more frequently recognized in celiac disease. Some have suggested that these may be due to an adenoma-carcinoma sequence,54 but others have reported that the risk of duodenal adenoma is not increased in celiac disease 81. Most occur in the proximal small intestine and may cause bleeding or obstruction.…”
Section: Other Cancersmentioning
confidence: 99%